Millisecond‐Range Time‐Resolved Bioimaging Enabled through Ultralong Aqueous Phosphorescence Probes. Issue 14 (15th February 2022) - Cui, Mingyue; Dai, Peiling; Ding, Jiali; Li, Manjing; Sun, Rong; Jiang, Xin; Wu, Menglin; Pang, Xueke; Liu, Mingzhu; Zhao, Qiang; Song, Bin; He, Yao
Abstract: Probes featuring room‐temperature phosphorescence (RTP) are promising tools for time‐resolved imaging. It is worth noting that the time scale of time‐resolved bioimaging generally ranges around the microsecond level, because of the short‐lived emission. Herein, the first example of millisecond‐range time‐resolved bioimaging is illustrated, which is enabled through a kind of ultralong aqueous phosphorescence probes (i.e., cyclo‐(Arg‐Gly‐AspD‐Tyr‐Cys)‐conjugated zinc‐doped silica nanospheres), with a RTP emission lasting for ≈5 s and a lifetime as long as 743.7 ms. We demonstrate that live cells and deep tumor tissue in mice can be specifically targeted through immune‐phosphorescence imaging, with a high signal‐to‐background ratio (SBR) value of ≈69 for in vitro imaging, and ≈627 for in vivo imaging, respectively. We further show that, compared to that of fluorescence imaging, the SBR enhancement of millisecond‐range time‐resolved in vivo bioimaging is up to 105 times. Abstract : A pioneering example of millisecond‐range time‐resolved bioimaging is illustrated, which is enabled through ultralong aqueous phosphorescence probes.